Adopting Technology in Preserving and Promoting Cultural Tourism - Sharina Osman (IAHN-TP Palangka Raya, 2023)
Cultural Heritage, both tangible and intangible, is an expression of a lifestyle, developed by a society and transmitted from generation to generation, which includes traditions, belief, space, object, artistic expression and value systems. Cultural and natural heritages are valuable resources that add to the unique tourism appeal of any country. Protecting and promoting heritage value as a valuable tourism product, on the other hand, is a difficult task. This paper discusses how technological advancements can help with the preservation and promotion of cultural heritage tourism. The study used Malaysia as a case study, providing a discussion of the intriguing potential surrounding virtual travel experiences obtained through MyVirtual Experience Programme participants' participation. In many respects, the usage of technological applications has benefited the visitor experience as well as the source of cash production for industry players.